2007
DOI: 10.1177/0011128706286554
|View full text |Cite
|
Sign up to set email alerts
|

Wrongful Conviction

Abstract: Drawing on a sample of 798 Ohio criminal justice professionals (police, prosecutors, defense attorneys, judges), the authors examine respondents' perceptions regarding the frequency of system errors (i.e., professional error and misconduct suggested by previous research to be associated with wrongful conviction), and wrongful felony conviction. Results indicate that respondents perceive system errors to occur more than infrequently but less than moderately frequent. Respondents also perceive that wrongful felo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In Canada, Doob (1997) found that nearly half of the criminal defence lawyers sampled believed that they had represented a client who had been wrongfully convicted and sentenced to at least 1 year in prison. Moreover, estimates of wrongful conviction rates range from 0.5% to 15% (or more) of all convictions, suggesting that thousands of innocent citizens are wrongfully imprisoned every year (e.g., Huff, Rattner, & Sagarin, 1996;Poveda, 2001;Ramsey & Frank, 2007;Zalman, Smith, & Kiger, 2008).…”
mentioning
confidence: 99%
“…In Canada, Doob (1997) found that nearly half of the criminal defence lawyers sampled believed that they had represented a client who had been wrongfully convicted and sentenced to at least 1 year in prison. Moreover, estimates of wrongful conviction rates range from 0.5% to 15% (or more) of all convictions, suggesting that thousands of innocent citizens are wrongfully imprisoned every year (e.g., Huff, Rattner, & Sagarin, 1996;Poveda, 2001;Ramsey & Frank, 2007;Zalman, Smith, & Kiger, 2008).…”
mentioning
confidence: 99%
“…Wrongful conviction scholars acknowledge that the exoneration counts likely represent a fraction of all wrongful convictions, and the actual rate of such convictions "is not merely unknown but unknowable" (Gross, O'Brien, Hu, & Kennedy, 2014, p. 7230). Thus, researchers have estimated wrongful conviction rates based on analyses of death-penalty convictions (Gross et al, 2014;Gross & O'Brien, 2008;Risinger, 2007), the opinions of justice professionals (Ramsey & Frank, 2007;Zalman, Smith, & Kiger, 2008), postconviction DNA testing on archived biological evidence (Roman, Walsh, Lachman, & Yahner, 2012;Walsh, Hussemann, Flynn, Yahner, & Golian, 2017), and inmate self-report data (Loeffler, Hyatt, & Ridgeway, 2019;Poveda, 2001). For example, recent analyses have produced estimates ranging from 4.1% in death-sentenced defendants (Gross et al, 2014), 6% in inmates serving noncapital felony sentences in Pennsylvania (Loeffler et al, 2019), to more than 11% in 1970s and 1980s convictions involving sexual assault in Virginia (Walsh et al, 2017).…”
Section: Counting Wrongful Convictionsmentioning
confidence: 99%
“…According to Huff, Rattner & Sagarin (1996), the number of wrongful convictions of innocent people in the USA ranges from one half to one percent of the total number of indictments. Ramsey & Frank (2007) cite a higher number, namely, from one to three percent. Risinger (2007), whose estimation is based on data from the American "Innocence Project", claims that the number of wrongful convictions among those who were convicted of the combined offences of rape and murder and were sentenced to death lies between a minimum of 3.3 percent and a maximum of 6.6 percent.…”
Section: Introductionmentioning
confidence: 99%